CULTURAL CAPITAL AS TOURISM DEVELOPMENT BASIS IN TRADITIONAL VILLAGE OF KUTA - Sumadi, Ketut; Ardika, I Wayan; Kutha Ratna, I Nyoman; Mariyah, Emiliana (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2010)
Tourism is a favourite sector in improving Bali revenue and kind of tourismdeveloped is cultural one. In cultural tourism, it takes place meaning modification ofcultural practice by krama (member) of traditional village) in order to cultural capitalcan survive in the middle of tourism dynamic condition. This research entitled“Cultural capital as tourism development basis in traditional village of Kuta”, byproposing three problems, namely how is the process of cultural capital as tourismdevelopment basis, what factors can motivate tourism capital as tourism developmentbasis, and what is the meaning of cultural capital as tourism development basis.The research is conducted using qualitative method and cultural studiesapproach, so data analysis is conducted in descriptive qualitative and interpretativeones. Selection of traditional village of Kuta as research location based onconsideration that traditional village of Kuta having integrated tourism facilities forfacilities addressed to member of traditional village. The review about culturalcapital as the tourism development basis in this traditional village of Kuta, eclecticstheories consisting of Hegemonic theory of Gramsci, co-modification theory of KarlMarx and Adorno, discourse-power/knowledge and truth theory of Foucoult anddeconstruction theory of Derrida.Based on the research output, it can be known: (1) Cultural capital process astourism development basis in traditional village of Kuta is inseparable fromforeigners arrival in traditional village of Kuta, the entrance of Military (TheCooperative Center of Arm Force) in managing Kuta beach and the occurrence ofBali bombing tragedy on October 12th, 2002; (2) The factors that motivate culturalcapital as the tourism development basis in traditional village of Kuta, such asmotivation and the necessity of tourists visiting traditional village of Kuta, tourismhegemony, changing of life philosophy of member of traditional village fromidealism into pragmatism one and the image as global village; (3) Cultural village astourism development basis in traditional village of Kuta has innovation, religious,preservation of cultural, political identity and prosperity meanings.Behind the success of cultural capital as tourism development basis, itimproves live prosperity, and also it causes negative effect such as there is krama(member) of traditional village for losing their cultural capital. They aremarginalized in economic field as they have no cultural capital in term of knowledgeand skill in tourism area and it is said to be “kidang nyirig pangkung”; they cannot utilize the opportunity of tourism market well. As consequence in traditional villageof Kuta, there are still poor families and they have no suitable housing.